The translation accuracy in children story dorothy and mikey - Nunun Tri Widarwati; Purwani Indri Astuti; Ratih Wijayava (English Teaching Journal : A Journal of English Literature, Language and Education, 2022)
The study aims to find the quality of translation children story by the theme “Dorothy and Mikey” from English to Indonesian. The Study used qualitative method by using accuracy of translation. Data used all of senteces in the pictures children story the tittle is “Dorothy and Mikey”. Sources of data contain document, children story book in English and it translation. We used forum group discussion to analyze document. The findings that 82 data or 84,54% accurate and 15 data or 15,46% less accurate in the Dorothy and Mikey story.